Making the best of aggression, the many dimensions of bacterial toxin regulation - Gonzalez,D; Mavridou,D (Trends in Microbiology, 2019)
Most bacteria use toxins to exclude competitors.As the synthesis and delivery of these moleculesentail considerablecostsfor the producers, theirexpressionis tightly regulated, often by molecular systems detecting physiological stressesor environment-specific cues.However, the ecological connection between such systemsand competitive behaviorsis not always clear. Here, we review the regulation of antibacterial toxins and propose a conceptual framework organizing the decision-making processes controlling toxin production. As bacteria are unable to precisely identify their competitors,we argue that toxin regulation primarily responds to cues directly or indirectly associated with the presence of competing strains. The density and fitnessof the producing populational so play a role in the decision-making process.Overall, we contendthat optimal toxin production strategies involvemonitoring of both self and foe.